Sistem Pemantauan Kedisiplinan Santri Berbasis Citra Raspberry Pi Dan Internet Of Things - Qadri, Khaerul; Razak, Mashur; Jalil, Abdul (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2025)
The pesantren, as a traditional Islamic educational institution, faces significant challenges in maintaining discipline due to the large number of students and the extensive area. To address these challenges, an innovative discipline monitoring system using Internet of Things (IoT) technology, Raspberry Pi, and image recognition has been developed. This system employs a webcam connected to the Raspberry Pi to capture and analyze students' faces, activating a buzzer in response to detected disciplinary patterns. The system was installed in strategic locations, with real-time audio responses provided by the buzzer and data processed and recorded via a web-based platform. Analysis of the system's performance reveals that violations most frequently occur in the afternoon, accounting for 45.7%, followed by daytime violations at 30.4%. The system demonstrates high accuracy, efficiency, and reliability in detecting and managing disciplinary issues. These findings, illustrated in the accompanying charts and pie diagram, underscore the system’s operational efficiency, high detection accuracy, and effective data management capabilities, significantly enhancing discipline management and the overall quality of education in the pesantren.